c-Jun-N-Terminal Kinase Signaling Is Involved in Cyclosporine-Induced Epithelial Phenotypic Changes - Nicolas Pallet; Eric Thervet; Dany Anglicheau (Journal of Transplantation)
Tubular epithelial cells play a central role in the pathogenesis of chronic nephropathies. Previous toxicogenomic studies have demonstrated that cyclosporine- (CsA-) induced epithelial phenotypic changes (EPCs) are reminiscent of an incomplete epithelial to mesenchymal transition (EMT) in a TGF-β-independent manner. Furthermore, we identified endoplasmic reticulum (ER) stress as a potential mechanism that may participate in the modulation of tubular cell plasticity during CsA exposure. Because c-jun-N-terminal kinase (JNK), which is activated during ER stress, is implicated in kidney fibrogenesis, we undertook the current study to identify the role of JNK signaling in EPCs induced by CsA. In primary cultures of human renal epithelial cells, CsA activates JNK signaling, and the treatment with a JNK inhibitor reduces the occurrence of cell shape changes, E-cadherin downregulation, cell migration, and Snail-1 expression. Our results suggest that CsA activates JNK signaling, which, in turn, may participate in the morphological alterations through the regulation of Snail-1 expression.